1982
DOI: 10.1046/j.1537-2995.1982.22482251219.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion therapy and HLA antibody response in patients undergoing open heart surgery

Abstract: HLA antibody formation was studied in 212 patients undergoing open-heart surgery on cardiopulmonary bypass in relation to the following variables: sex, obstetric history, transfusion history, quantity and nature of blood products transfused, type of oxygenator used, duration of bypass, and time of assay. Postoperative alloimmunization was seen in 33.6 percent of males and 64.3 percent of females. Previous pregnancy seemed to favor the development of antibody. No statistically significant correlation was noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
9

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 7 publications
1
23
1
9
Order By: Relevance
“…Conclusion: There was a low incidence of platelet-specific antibodies after one series of blood transfusions in this group of patients. This is similar to the results of some previous studies in multiply transfused patients, but not with those of others who found a higher incidence.tients receiving multiple transfusions [5][6][7][8], The occur rence of HLA antibodies after one series of transfusion ther apy has previously been found to be very frequent [9,10].We have performed a prospective study in order to deter mine the frequency and the specificity of platelet alloantibodies in individuals who received one series of blood transfusions with mainly SAG-M (saline adenine glucose + mannitol) red cell blood products in connection with car diac surgery. …”
supporting
confidence: 90%
See 1 more Smart Citation
“…Conclusion: There was a low incidence of platelet-specific antibodies after one series of blood transfusions in this group of patients. This is similar to the results of some previous studies in multiply transfused patients, but not with those of others who found a higher incidence.tients receiving multiple transfusions [5][6][7][8], The occur rence of HLA antibodies after one series of transfusion ther apy has previously been found to be very frequent [9,10].We have performed a prospective study in order to deter mine the frequency and the specificity of platelet alloantibodies in individuals who received one series of blood transfusions with mainly SAG-M (saline adenine glucose + mannitol) red cell blood products in connection with car diac surgery. …”
supporting
confidence: 90%
“…HLA antibodies after one series of blood transfusions have previously been demonstrated in 46-74% of the patients undergoing open heart surgery [9,10]. The explanation for this discrepancy could be due mainly to a minor load of immunogenic materials trans fused to the patients in our study than in the previous re ports, where red blood cell concentrates and WB have been used.…”
Section: Immunological Datamentioning
confidence: 52%
“…Most of these disappearing antibodies were not IgG antibodies. Disappearance of panel reactivity in spite of or because of transfusions was previously reported in literature 5,15,16 . Most reports are about disappearance of induced antibodies in repeatedly transfused patients receiving immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 81%
“…1,[3][4][5][6][7][8][9] These antibodies are usually detected within the first 2 weeks after exposure and can be either short-lived or persist long after transfusion. 3,4,[10][11][12][13] Leukoreduction of platelets has been shown in most studies to reduce the frequency of, but not eliminate, alloimmunization, 3,[5][6][7][8]14 although not necessarily in previously pregnant recipients. 15 Rates are higher in previously pregnant women or those who have been transfused before.…”
Section: Introductionmentioning
confidence: 99%
“…15 Rates are higher in previously pregnant women or those who have been transfused before. 7,9,10,16 A number of methods have been used to measure HLA Abs. Originally, this was done using the lymphocytotoxicity assay (LCA), in which cells expressing the HLA protein of interest are incubated with the serum sample to be screened and lysis of these target cells is measured.…”
Section: Introductionmentioning
confidence: 99%